Validating the Use of Performance Risk Indices for System-Level Risk and Maturity Assessments. Issue 2 (2nd April 2016) - Holloman, Sherrica S.; Stuban, Steven M. F.; Dever, Jason
Abstract: The Mahafza, Componation, and Tippett (2005) Technology Performance Risk Index (TPRI) ties the assessment of technical performance to the quantification of the risk of unmet performance; however, its input is structured for component-level data. This study's first goal is to establish a modified TPRI using systems-level data as input. The second goal is to then validate the modified index with actual system-level data from the Department of Defense's Major Defense Acquisition Programs. This work's contribution is the establishment and validation of the System-level Performance Risk Index.